Antibacterial mechanism of beetroot (Beta vulgaris) extract against Listeria monocytogenes through apoptosis-like death and its application in cooked pork. (1st August 2022) - Gong, Shaoying; Jiao, Chaoqin; Guo, Ling
Abstract: Due to riching in polyphenolic compounds, betalains, and ascorbic acid, beetroot ( Beta vulgaris ) extract exhibits an antibacterial activity. However, its effect on Listeria monocytogenes is unclear. In this study, the antibacterial activity of beetroot extract against L. monocytogenes was assessed by measuring its minimum inhibitory concentration (MIC) and the time-kill curve. Results revealed that the MIC of beetroot extract against L. monocytogenes was 20 mg/mL and bacterial survival decreased as beetroot extract concentration increased. The antibacterial mechanism of beetroot extract involved the reduction of intracellular 5ʹ-adenosine triphosphate levels of L. monocytogenes after treatment. L. monocytogenes exhibiting membrane depolarization, caspase-like protein activation, phosphatidylserine externalization, and DNA fragmentation, demonstrated that L. monocytogenes underwent apoptosis-like death (ALD) following beetroot extract treatment. Furthermore, the reason of ALD in L. monocytogenes is reactive oxygen species depletion. Beetroot extract decreased the number of L. monocytogenes cells, pH values, and lipid oxidation in cooked pork. Meanwhile, cooked pork become darker and redder than the control samples. It suggested that beetroot extract could be used as a natural preservative in cooked meat production to inhibit the growth of L. monocytogenes . Highlights: Beetroot extract (BE) can inhibit the growth of Listeria monocytogenes. BE reduced intracellular ATP levels of L. monocytogenes. BE caused apoptosis-like death in L. monocytogenes by depleted ROS level. BE caused the decrease of L. monocytogenes counts and pH values in cooked pork. BE delayed lipid oxidation in cooked pork.